Counseling On The Provision Of Complementary Feeding Foods To Prevent Diarrhea In Toddlers In West Mamboro: Penyuluhan Pemberian MP-ASI Mencegah Diare Pada Balita Di Kelurahan Mamboro Barat - Nurjaya Nurjaya; Nur Amalia; Syukur; Abd Farid Lewa (Jurnal Pengabdian Masyarakat: Svasta Harena, 2022)
Provision complementary feeding is one of the factors that influence the incidence of diarrhea. There are various reasons, including unhygienic formula feeding and early complementary feeding. Lack of knowledge of mothers in provision Complementary feeding can have an impact on the health of toddlers, one of which is toddlers will often experience diarrhea. The purpose of this community service is to provide additional knowledge of mothers under five in the provision of Complementary feeding to help prevent diarrhea in children. This service is carried out by providing counseling. The results of this activity indicate an increase in the knowledge of mothers under five about the provision of Complementary feeding. The percentage of mothers under five with good knowledge at the pre-test was 76,7% and mothers under five with good knowledge increased to 94,5% after attending the counseling. Increased knowledge of mothers under five can help improve skills in determ